2019
DOI: 10.1093/sleep/zsz154
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in Huntington’s disease: a systematic review and meta-analysis of polysomongraphic findings

Abstract: Study Objectives Disturbed overnight sleep is a prominent feature of advanced stage Huntington’s disease (HD). Several polysomnography (PSG) studies have reported significant changes of sleep in HD patients, but the findings are not unequivocal. To date, no meta-analysis has investigated the PSG changes in HD patients. The present study meta-analyzed results from studies examining the PSG changes in HD patients compared with controls. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…However, a recent meta-analysis [ 60 ] of these studies has helped to address this. This identified the consistent sleep architecture abnormalities of HD as being those of reduced sleep efficiency, increased time awake after sleep onset, delayed REM sleep onset, and an increased proportion of time spent in the lightest stage of sleep (N1) versus a reduction of time spent in slow wave sleep and REM sleep.…”
Section: Sleep and Circadian Abnormalities In Huntington’s Disease: Evidence To Datementioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent meta-analysis [ 60 ] of these studies has helped to address this. This identified the consistent sleep architecture abnormalities of HD as being those of reduced sleep efficiency, increased time awake after sleep onset, delayed REM sleep onset, and an increased proportion of time spent in the lightest stage of sleep (N1) versus a reduction of time spent in slow wave sleep and REM sleep.…”
Section: Sleep and Circadian Abnormalities In Huntington’s Disease: Evidence To Datementioning
confidence: 99%
“…Cross-sectional studies of premanifest and early stage HD patients have revealed such sleep architecture abnormalities to be present many years prior to manifest disease, and to worsen with approaching manifest disease onset [ 39 , 42 , 44 ]. Among the subsequent manifest HD population, sleep abnormalities appear to continue to progress in parallel with increasing disease severity [ 44 , 57 , 60 ]. Again this mirrors findings in Alzheimer’s and Parkinson’s [ 61 , 62 ].…”
Section: Sleep and Circadian Abnormalities In Huntington’s Disease: Evidence To Datementioning
confidence: 99%
“…Circadian dysfunction is also common throughout, as evidenced by loss of robust rest-activity rhythms, abnormalities of melatonin concentration and rhythmicity, and loss of autonomic diurnal fluctuation [37,38]. Likewise, where sleep architecture is analyzed via polysomnography, a characteristic pattern of abnormalities emerges, that of increased arousals/ awakenings, loss of slow-wave and rapid eye movement (REM) sleep stages, increased latency to initiation of REM, and consequent gain in time spent in the lightest stages of sleep [35,[39][40][41]. It is also notable that, across the spectrum of neurodegenerative disease, sleep abnormalities frequently precede diagnostic clinical features: for example, sleep fragmentation precedes the onset of overt Alzheimer's disease and manifest Huntington's disease [42,43] and REM behavior sleep disorder (RBD) often precedes the clinical onset of motor features of Parkinson's, multiple system atrophy, or Lewy body dementia [44,45].…”
Section: Sleep Dysfunction In Neurodegenerative Conditions: Commonalimentioning
confidence: 99%
“…Sleep disturbances are common in HD and affect up to 90% of patients. Despite its common occurrence in HD, sleep disorders have not been so thoroughly investigated as in other neurodegenerative disorders ( Zhang et al, 2019 ). Although disturbed sleep in HD correlated with its severity and duration of illness, poor sleep has been reported in the early stages of the disease, even among asymptomatic carriers of the HD mutation ( Arnulf et al, 2008 ; Lazar et al, 2015 ).…”
Section: Sleep Dysfunction In Neurodegenerative Disordersmentioning
confidence: 99%